Chapati Making Quality of Whole Wheat Flour (Atta) Obtained by Various Processing Techniques. Issue 6 (11th September 2015) - Inamdar, Aashitosh A.; Sakhare, Suresh D.; Prabhasankar, P.
Abstract: Wheat was processed in chakki (CM), hammer (HM), disk (DM), pin (PM) and roller mill (RM) with an objective of quality characterization of whole wheat flour ( atta ) in relation to chapati making quality. Results indicated atta produced from RM was cooler and had retained more moisture. Ash content was not significantly influenced by different grinders; however, acid insoluble ash was higher at 0.063% for the atta produced from CM. Variation in damaged starch was observed which was 15.99, 13.76, 11.76, 10.16 and 9.1% for CM, HM, DM, PM and RM ground atta, respectively. Farinograph water absorption of CM ground atta was highest at 85% and least for RM ground atta (71.5%). Overall quality of chapati prepared from CM atta scored higher and had better texture and desirable wheaty aroma. Studies revealed that atta quality parameters and its chapati making quality varied with processing techniques. Practical Applications: Out of around 94 million metric tons wheat produced in India annually, about 50–55 million metric tons (MMT) is processed to obtain atta . This makes atta one of the major products made from the wheat, and is consumed mainly in the form of chapati. Traditionally, Indian families process a smaller quantity of atta in the chakkis, a pair of stone mills and consume fresh. This practice is however slowly dying in the larger cities as they are opting for packaged atta because of busy lifestyles and increased disposable income. Packaged atta industry is witnessing a growth of 25% annually. Because of the increased demand, there is a need to have more options for the higher capacity production of atta, and the study is carried with an objective to study effects of various processing techniques on different quality characterization of whole wheat flour ( atta ) in relation to its chapati making quality.